Realising Female Inheritance Rights in South Eastern Nigeria: The Imperativeness of Going beyond Legal Rhetoric - Eyongndi, David Tarh-Akong; Opara, Faith Nwayemogho; Oladele, Olayiwola Owoade; Agbu, David Andrew; Ajayi, Mary-Ann Onoshioke (The Age of Human Rights Journal, 2024)
The decision of the Supreme Court of Nigeria in Ukeje v. Ukeje is regarded as the ultimate liberation of females, particularly in Eastern Nigeria from discriminatory customary law which disentitles them from inheritance in cases of intestate succession. While this decision buttresses the non-discriminatory provision of section 40 of the 1999 Constitution of the Federal Republic of Nigeria, making a judicial pronouncement is different from giving effect to same. The question, therefore, is how can this decision be effectuated especially in rural areas where the people jealously guard their traditional beliefs, values and customary practices? This paper, through desk-based method with reliance on primary and secondary sources of data, interrogates how the discriminatory inheritance cultural beliefs (volksgeist) and practices of the Igbo people can be synergised with the decision in Ukeje v. Ukeje. It argues that this will require extra-legal mechanisms like gender equality sensitisation campaigns, communal reorientation through enlightenment, and dialogue with traditional institutions. It therefore recommends dialoguing with traditional institutions and reorienting the community as measures to be adopted in effectuating the judgment in the rural Igbo communities where same is opposed to their volksgeist towards fostering gender equality which is central to Sustainable Development Goal 5.